Protein Delivery System Containing a Nickel‐Immobilized Polymer for Multimerization of Affinity‐Purified His‐Tagged Proteins Enhances Cytosolic Transfer. (31st July 2015) - Postupalenko, Viktoriia; Desplancq, Dominique; Orlov, Igor; Arntz, Youri; Spehner, Danièle; Mely, Yves; Klaholz, Bruno P.; Schultz, Patrick; Weiss, Etienne; Zuber, Guy
Abstract Recombinant proteins with cytosolic or nuclear activities are emerging as tools for interfering with cellular functions. Because such tools rely on vehicles for crossing the plasma membrane we developed a protein delivery system consisting in the assembly of pyridylthiourea‐grafted polyethylenimine (πPEI) with affinity‐purified His‐tagged proteins pre‐organized onto a nickel‐immobilized polymeric guide. The guide was prepared by functionalization of an ornithine polymer with nitrilotriacetic acid groups and shown to bind several His‐tagged proteins. Superstructures were visualized by electron and atomic force microscopy using 2 nm His‐tagged gold nanoparticles as probes. The whole system efficiently carried the green fluorescent protein, single‐chain antibodies or caspase 3, into the cytosol of living cells. Transduction of the protease caspase 3 induced apoptosis in two cancer cell lines, demonstrating that this new protein delivery method could be used to interfere with cellular functions.